Estratégias de gerenciamento para dor lombar na primeira linha de cuidado da atenção primária - Silva Junior, Denis Macleam Cunha (2024)
Low back pain (LBP) is a leading cause of global disability, with an increasingly significant impact in low- and middle-income countries. In Brazil, Primary Health Care (PHC) plays a central role in managing LBP, making adherence to evidence-based clinical guidelines essential for mitigating the socioeconomic burden of this condition. This dissertation aimed to investigate the strategies employed in the management of LBP within the first level of care in PHC. The study comprises two scientific outputs. The first output examined the adherence of PHC physicians and nurses in Fortaleza, Brazil, to clinical guidelines for LBP management and the factors associated with such adherence. A cross-sectional study involving 146 PHC physicians and nurses was conducted, utilizing the analysis of two simulated clinical cases. Healthcare professionals were classified as adherent if they exclusively selected therapeutic options recommended by the guidelines, and as non-adherent if they chose at least one unsupported or non-recommended intervention. The results revealed low adherence rates for both acute (29.1%) and chronic LBP (12.3%), highlighting critical gaps in evidence-based practice. Furthermore, the study identified that professional role and the integration of environmental factors into the patient care approach were associated with guideline adherence. The second output focused on describing and analyzing the accuracy of the information provided in the Brazilian Ministry of Health’s national care pathway for LBP management in PHC. Recommendations on non-pharmacological and pharmacological treatments, as well as general care guidance, were extracted from the national care pathway and compared against current international guidelines to assess accuracy. Each management recommendation was independently analyzed by two researchers and classified as accurate, partially accurate, inaccurate, or not mentioned, based on the clarity and precision of the information provided. The analysis revealed that 43% of the recommendations were accurate, 30% partially accurate, and 26% not mentioned. Notably, general care guidance showed only 14% accuracy, whereas non-pharmacological interventions achieved a 60% accuracy rate. These findings underscore the need for continuous updates to the care pathway, particularly in general care guidance and non-pharmacological strategies. This dissertation highlights the discrepancy between clinical recommendations and practice, suggesting the need for implementation studies on continuing education for PHC professionals regarding LBP management. Given that the care pathway can serve as an ally in this process, this study recommends periodic updates to the Brazilian Ministry of Health’s care pathway for LBP management. By identifying gaps in evidence-based practice and proposing strategies for professional development, this study holds the potential for significant scientific and social impact, aiming to reduce disability and enhance functionality in individuals with LBP in Brazil.